Pengaruh Faktor Keluarga dan Stigma Masyarakat Terhadap Kekambuhan Pasien Skizofrenia di Yayasan Galuh Kota Bekasi - Ahmad Farid Umar; Elwindra Elwindra; Supriyanto Supriyanto (Jurnal Persada Husada Indonesia, 2017)
Schizophrenia is one of the most serious mental disorders that occur in all societies. The recurrence of schizophrenic patients is high and costly, borne by families and governments. Recovered schizophrenic patients are not supposed to experience recurrence. This study aims to determine the influence of family factors and community stigma on the recurrence of patients with schizophrenia in Galuh Foundation Bekasi City carried out between May to July 2016. This study was based on qualitative method with Phenomenology approach. Purposive Sampling method was used in the sample collection, a method based on a specific consideration such as the recognized characteristics of the population. In this study there were three types of informants, the number of samples used amounted to 6 people consisting of 2 schizophrenia patients, 2 health workers and 2 families of patients. Data collection technique uses in-depth interviews, observation, and document review. Data validity examination technique uses uses triangulation method of data source. The results showed that factors in the family and stigma of the community can affect the occurrence of recurrence in schizophrenic patients. Suggestions to the Health Office, Social Service and Galuh Foundation Bekasi City to cooperate with the families of patients and the general public in an effort to eliminate the stigma and discrimination towards patients to avoid the occurrence of recurrence.